The time of logos. Considerations on the systematic place of the history of philosophy in Hegel - Duque, Félix (Estudios de Filosofía, 1996)
lt is maintained here that the History of Philosophy propases a tension benveen time and logos, and that understanding that tension there properly leads to clarify its role in philosophy. This thesis is developed by studying the place such a discipline us given in the Hegelian system. lt is thought here that the interdependence of time and logos must be evidenced in a double way. On the one hand, it is necessary to consider the existence (Dasein) of concept in the time, and on the other hand, how difficult it is for philosophy to clarify the historie time in the concept. Accordingly, although Hegel is aware of the importance of The History of Philosophy for achieving his system (as far as "knowing about the historie coming to be of philosophy is philosophy too), he emphasises logos. Against the Hegelian propasal, it is stated that philosophical texts must not be regarded as a "mere product of their time" and thence it is unavoidable lo accept a fundamental opacity that produces the equivocity of such texts.